2021
DOI: 10.1002/mrm.28833
|View full text |Cite
|
Sign up to set email alerts
|

Sources of systematic error in DCE‐MRI estimation of low‐level blood‐brain barrier leakage

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…However, validation would be required to determine how representative such metrics are of the vascular surface area. In-silico methods are also a promising approach to evaluate the influence of different noise sources, acquisition, and analysis strategies at minimal cost ( Bernal et al, 2021 , Manning et al, 2021 ). While promising non-contrast based imaging MRI-based techniques, including diffusion-weighted arterial spin labelling, require further development, particularly to improve the limited SNR in white matter.…”
Section: Discussionmentioning
confidence: 99%
“…However, validation would be required to determine how representative such metrics are of the vascular surface area. In-silico methods are also a promising approach to evaluate the influence of different noise sources, acquisition, and analysis strategies at minimal cost ( Bernal et al, 2021 , Manning et al, 2021 ). While promising non-contrast based imaging MRI-based techniques, including diffusion-weighted arterial spin labelling, require further development, particularly to improve the limited SNR in white matter.…”
Section: Discussionmentioning
confidence: 99%
“…A dynamic contrast-enhanced MRI (DCE-MRI) [ 63 ] has been employed for in-vivo quantification of the pathological passage of plasma through BBB [ 64 , 65 ]. Moreover, apart from the BBB leakage, the possibility of estimating the vascular permeability-surface area product (PS) and the plasma volume fraction (VP) in a given region of interest has also been described [ 66 , 67 ].…”
Section: Possible and Proved New Markers Of Blood–brain Barrier Leaka...mentioning
confidence: 99%
“…Moreover, apart from the BBB leakage, the possibility of estimating the vascular permeability-surface area product (PS) and the plasma volume fraction (VP) in a given region of interest has also been described [ 66 , 67 ]. The model suggested that PS increased with WMH severity, aging, and other vascular risk factors, and at the same time, a lower blood vP [ 65 ]. The most promising in-vivo demonstration is that BBB integrity is compromised in more severe WMH, even beyond visible lesions [ 63 ] (Insert Figure 1 ).…”
Section: Possible and Proved New Markers Of Blood–brain Barrier Leaka...mentioning
confidence: 99%
“…The direct method, high resolution dynamic contrast enhancement/imaging (DCI or DCE), is to image the presence of fluid leaking past the BBB into the interstitium, either by direct or indirect means. DCE is a post gadolinium contrast infusion technique [35][36][37][38][39][40][41]. It utilizes fast image acquisition to sequentially measure the entrance of contrast into the field of view and it can determine a variety of physiologic parameters related to blood flow and perfusion [42].…”
Section: Yes Lowmentioning
confidence: 99%